The effect of mechanical cues on the chondrogenic differentiation of bone marrow derived mesenchymal stem cells - Thorpe, Stephen (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2012)
Tissue engineering strategies utilising mesenchymal stem cells (MSCs) represent a promising treatment option for a range of injuries and diseases. If MSCs are to be implanted in vivo, understanding the intricacies of how their multipotent characteristics are controlled is vital. One regulator of MSC differentiation is biomechanical stimulation. A central hypothesis of this thesis is that mechanical stimulation can direct the chondrogenic differentiation and functional chondrogenesis of MSCs. Herein, the research examines the response of hydrogel encapsulated MSCs to dynamic compressive strain.
Keywords: Bioengineering, Ph.D.; Ph.D. Trinity College Dublin.